EFL Vocational School Teachers’ Non-Verbal Behaviors in Teaching English - Alviyyah, Thallah; Maharsi, Ista (Universitas Pahlawan Tuanku Tambusai, 2025)
This paper affirms that communication theory in nonverbal behaviour is critical in conveying messages in social relations. In EFL classroom contexts, non-verbal behaviours remain important as they can assist both teachers and students during the learning process. This paper explores the types of non-verbal behaviors utilized by EFL teachers in teaching English in a vocational school. This study was designed as an observational study. Data were collected from a classroom video segment of 29 minutes which was observed and the categorization of gesture forms was adopted from Wang and Loewen (2016). This study finds that non-verbal behaviors such as metaphoric, emblems, affect displays, deictic, beats, head movement, and iconic were produced by the teacher participant. The findings indicate that the use of non-verbal behaviors supports the natural role of learning in the classroom, which is crucial for helping students understand language in the classroom.